A Política Fiscal à Proteção Florestal no Contexto das Sociedades Portuguesas - Dinis, Ana (2024)
This article aims to study the fiscal incentives for forest protection in Portugal. Understanding the reality of this fiscal policy is fundamental in the context of sustainable forest management. After reviewing the literature focused on the importance of the forest as an essential asset to meet human needs, the Portuguese tax regime in this area is analysed. This is followed by a study of tax incentives for Forest Intervention Areas (FIA) and Forest Management Plans (FMP) in the Portuguese business context in the period 2015-2020. The main results of the research show that companies connected to the sector have become more aware of the importance of adopting more sustainable practices, by adhering to these tax benefits over time, showing the role of environmental tax policy in the sustainable growth of the economic tissue. The results show that the number of beneficiary companies is reduced compared to the total number of companies operating in the forestry sector in Portugal, also verifying that most of these companies are concentrated in a small number of municipalities, some of which have no FIA. There is still important work to be done with a view to greater dissemination of the tax benefits under study.